Media and Information Literacy of Elderly Individuals - a Prerequisite for Participation in the Digital Era - Trninić, Dragana (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
Thanks to the continuous development of information and communication technologies (ICT), there are significant opportunities for easier everyday activities and problem-solving, particularly suitable for the elderly, from home delivery to bill payment to a higher-quality information system. One of the challenges of the modern digital age is organizing a society based on respect for human dignity, freedom, democracy, equality, where everyone can live and age without discrimination. Digital transformation potentially influences these processes and challenges. Given that almost half of individuals over 65 years old in Bosnia and Herzegovina (BaH) are in the digital divide, meaning they do not use the internet or digital services (CRA, 2021), this study focuses on this population, their media and information literacy (MIL). The aim is to determine the level of knowledge and skills of older adults in the field of MIL, which media they use and why, whether they trust them, and their attitude towards media and media content. The research was conducted in Republic of Srpska using the semi-structured interview method with 15 participants. The results indicate an insufficiently developed system of personal MIL competencies among the participants and the need for education of the elderly in this area, especially in the segment of digital competencies.